Effects of Lutein and Zeaxanthin on LPS-Induced Secretion of IL-8 by Uveal Melanocytes and Relevant Signal Pathways - Shih-Chun Chao; Tommaso Vagaggini; Chan-Wei Nien; Sheng-Chieh Huang; Hung-Yu Lin (Journal of Ophthalmology)
The effects of lutein and zeaxanthin on lipopolysaccharide- (LPS-) induced secretion of IL-8 by uveal melanocytes (UM) were tested in cultured human UM. MTT assay revealed that LPS (0.01–1 μg/mL) and lutein and zeaxanthin (1–10 μM) did not influence the cell viability of cultured UM. LPS caused a dose-dependent increase of secretion of IL-8 by cultured UM. Lutein and zeaxanthin did not affect the constitutive secretion of IL-8. However, lutein and zeaxanthin decreased LPS-induced secretion of IL-8 in cultured UM in a dose-dependent manner. LPS significantly increased NF-κB levels in cell nuclear extracts and p-JNK levels in the cell lysates from UM, but not p-p38 MAPK and p-ERG. Lutein or zeaxanthin significantly reduced LPS-induced increase of NF-κB and p-JNK levels, but not p38 MAPK and ERG levels. The present study demonstrated that lutein and zeaxanthin inhibited LPS-induced secretion of IL-8 in cultured UM via JNK and NF-κB signal pathways. The anti-inflammatory effects of lutein and zeaxanthin might be explored as a therapeutic approach in the management of uveitis and other inflammatory diseases of the eye.